Aspek Wanprestasi Dalam Kasus Penghindaran Pajak Oleh PT. ABC Dalam Kontrak Kerja Sama - H.Arron Daud Unas; Shirley Wijaya; Kristi Indriyani (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This study finds that manipulating tax reports constitutes a breach of contract under a service cooperation agreement between PT. ABC and PT. XYZ. The breach occurred when PT. ABC underreported revenue received from PT. XYZ to the Regional Financial and Revenue Management Agency (BPKPD) to lower its tax obligations. The research adopts a normative legal methodology with a case study approach. Data were collected from contract documents, regional tax audit findings, court decisions at various levels, and relevant legal and accounting literature. A conceptual and statutory approach was applied to examine the legal implications of inaccurate tax reporting and its link to financial accounting principles. Findings indicate that tax manipulation in this case involves two violations: (1) breach of fiscal obligations, and (2) contractual default due to failure to meet agreed tax responsibilites. From an accounting standpoint, it breaches faithful representation and reliability principles in reportiing. The case illustrates how information asymmetry enables unehtical conduct when one party controls financial data. This underscores the need for strong internal controls, audit mechanisms, and transparent contractual terms to prevent similar violations.